Neonatal Hypercalcemia Secondary to Subcutaneous Fat Necrosis Successfully Treated with Pamidronate: A Case Series and Literature Review - Samedi, Veronica Mugarab (AJP Rep, 2014)
Subcutaneous fat necrosis (SCFN) is a noninfectious panniculitis that occurs in term infants who experience significant distress in the 1st weeks of life, including hypoxic ischemic encephalopathy (HIE). Since the introduction of therapeutic hypothermia for HIE, there have been a few published case reports of SCFN, following this modality of treatment. Although, most cases of SCFN resolve spontaneously, SCFN may be associated with hypercalcemia, which may sometimes reach dangerous levels. Approaches used for the management of this potentially life-threatening condition, include hyperhydration, calciuric diuretics, corticosteroids, and in more resistant cases pamidronate, a bisphosphonate. We report our experience on the use of pamidronate in two cases of severe hypercalcemia associated with SCFN following therapeutic hypothermia for HIE. We believe that with increasing use of therapeutic hypothermia for HIE, clinicians are likely to encounter this condition more frequently.